2014
DOI: 10.1139/bcb-2014-0008
|View full text |Cite
|
Sign up to set email alerts
|

Astragalusmembranaceusmodulates Th1/2 immune balance and activates PPARγ in a murine asthma model

Abstract: Astragalus membranaceus, a traditional Chinese herb, has been used to improve airway inflammation and asthma. The present study investigated whether A. membranaceus has immunotherapeutic effects on asthma, a chronic inflammatory mucosal disease that is associated with excess production of IgE, eosinophilia, T helper 2 (Th2) cytokines, and bronchial hyperresponsiveness. An ovalbumin (OVA)-induced, chronic inflammatory airway murine asthma model was used to examine the status of pulmonary inflammation after the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 60 publications
2
19
0
1
Order By: Relevance
“…This study indicated that the level of PPAR‐γ mRNA expression and its activity were increased in the lung tissues of AM‐treated mice (S.‐M. Chen et al, ). Rosiglitazone (ROSI), an agonist for PPAR‐γ, causes a modest amelioration in the lung function of smokers with mild to moderate asthma (Spears et al, ).…”
Section: Omega‐3 Pufas Receptorsmentioning
confidence: 81%
“…This study indicated that the level of PPAR‐γ mRNA expression and its activity were increased in the lung tissues of AM‐treated mice (S.‐M. Chen et al, ). Rosiglitazone (ROSI), an agonist for PPAR‐γ, causes a modest amelioration in the lung function of smokers with mild to moderate asthma (Spears et al, ).…”
Section: Omega‐3 Pufas Receptorsmentioning
confidence: 81%
“…The pharmacological effects of active compounds of frequently used herbs on MG and related autoimmune disease are as follows: (1) Astragalus membranaceus: promoting the expression of transcription factor Forkhead box protein P3 (FoxP3) to up-regulate T regulatory cells (Tregs) (Qu et al, 2010; Jin et al, 2013), and decreasing cytokine expression such as IL-4 and IL-13 (Chen et al, 2014b; Zhao et al, 2016); (2) Radix Ginseng: increasing number of Tregs and inhibiting Th17 cell differentiation (Bae et al, 2012; Chen et al, 2014a; Jhun et al, 2014; Lee et al, 2015; Chen et al, 2016); (3) Bupleurum polysaccharides (BPs) from Radix Bupleuri: a decrease of autoantibodies and immunoglobulin G (IgG) (Wang et al, 2009; Table 5 ). (4) Huperzine A (HupA), isolated from Huperzia serrata and flavonoid derivatives from Buzhongyiqi Decoction exhibited anti-acetylcholinesterase effects (Orhan, 2013; Cui et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Notably, the included trials presented evidence of immunologic regulation effects in multiple models of autoimmune disease as follows: Astragalus membranaceus (Qu et al, 2010; Jin et al, 2013; Zhao et al, 2016), Ginsenoside Rp1, Ginsenoside Rb1, and Ginsenoside metabolite compound K (Bae et al, 2012; Chen et al, 2014a, 2016; Jhun et al, 2014) from Radix Ginseng increase number of Tregs through promoting Foxp3 expression and further an increase of endogenous Treg population, or the adaptive transfer of compatible exogenous and possibly autologous functional Tregs (Bae et al, 2012). Astragalus membranaceus can regulate a cytokine production of various immune cells (Chen et al, 2014b; Zhao et al, 2016). Ginsenoside Rb1 (Jhun et al, 2014), Ginsenoside Rg1, Ginsenoside Rh1, and 20( S )-protopanaxatriol (Lee et al, 2015) from Radix Ginseng can inhibit Th17 cell differentiation, and Ginsenoside Rb1 (Chen et al, 2016) regulates the expression of IL-10 and IL-4, BP from Radix Bupleuri reduced autoantibodies and IgG (Wang et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…For example, some nuclear receptors such as VDR and peroxisome proliferator‐activated receptor γ (PPARγ) are responsible for the induction of LL‐37 (Liu et al, ; Peyrin‐Biroulet et al, ). Recently, several researches suggested the regulating abilities of APS on PPARγ expression (Chen et al, ; Liu, Bai, Weng, Wang, & Li, ), which may contribute to APS‐mediated LL‐37 induction. Thus, it is necessary to investigate whether APS‐mediated action is due to the alternation of other signaling pathways including VDR and PPARγ, which will help us to more deeply understand the action mechanisms of APS.…”
Section: Discussionmentioning
confidence: 99%